Use of ISSR markers for cultivar identification in durum wheat - Pasqualone A.; Lotti C.; Bruno A.; De Vita P.; Di Fonzo N.; Blanco A. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
Current methods for varietal identification of durum wheat, based on seed protein analysis, have a limited effectiveness since protein polymorphism is not so high. Subsequently, new more polymorphic analytical methods are required to avoid the possibility of seed mixture or substitution of high quality varieties with poor quality ones in commercial transactions. The inter simple sequence repeats (ISSR) are a new kind of molecular marker involving PCR amplification of DNA by a single primer composed of a repeated sequence anchored at the 3 prime or 5 prime end by 2-4 arbitrary nucleotides. The aim of this work is to test the efficiency of ISSR markers to distinguish a set of 30 Italian durum wheat cultivars and 22 breeding lines. The efficiency was found very high and two primers were found sufficient to distinguish all the durum wheat cultivars examined.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)